2017
DOI: 10.1080/16546628.2017.1368321
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-reducing agents prevent sulforaphane-induced growth inhibition in ovarian cancer cells

Abstract: The inhibitory potential of sulforaphane against cancer has been suggested for different types of cancer, including ovarian cancer. We examined whether this effect is mediated by mitogen-activated protein kinase (MAPK) and reactive oxygen species (ROS), important signaling molecules related to cell survival and proliferation, in ovarian cancer cells. Sulforaphane at a concentration of 10 μM effectively inhibited the growth of cancer cells. Use of specific inhibitors revealed that activation of MAPK pathways by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…1A) was measured and compared with Sul (isothiocyanate), which is known to be a strong inducer of NQO1 [19]. Sul also effectively inhibited the growth of ovarian cancer cells in our previous study [18]. Cur (curcuminoid) and Res (stilbenoid) are natural phenols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A) was measured and compared with Sul (isothiocyanate), which is known to be a strong inducer of NQO1 [19]. Sul also effectively inhibited the growth of ovarian cancer cells in our previous study [18]. Cur (curcuminoid) and Res (stilbenoid) are natural phenols.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that endogenous antioxidant enzymes (e.g., NQO1) are induced in response to increased intracellular ROS levels or alteration of the cellular redox state [24, 26]. Sul-induced inhibition of the growth of cancer cells has been shown to be related to Sul-induced oxidation that can be prevented by a thiol-reducing agent [18].
Fig. 4Activation of mitogen-activated protein kinases (MAPKs) by food-derived polyphenols.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SFN induced apoptosis and increased S phase cells and G1 arrest in MDAH-2774 cells. Kim et al [ 179 ] reported the effect of SFN on cell growth at 72 h in OVCAR3, OVCAR4, OVCAR5, and SKOV3 cell lines and found that SFN was effective at inhibiting cancer cell growth via activation of p38 and ERK. In a separate study, SFN treatment over a 24 h period induced apoptosis in SKOV3 and A2780 ovarian cancer cell lines.…”
Section: Sulforaphane In Cancer Prevention and Interventionmentioning
confidence: 99%
“…Increasing evidence has shown that the isothiocyanate (ITC) compound sulforaphane (SFN) and its analogs have great potential to prevent the growth of various tumor cells, including those in lung cancer [17], skin cancer [18], colon cancer [19], breast cancer [20], and ovarian cancer [21]. Pharmacokinetic studies in both humans and animals have shown that SFN is metabolized via the mercapturic acid pathway, producing predominantly cysteinylglycine (SFN-CG), cysteine (SFN-Cys), and N-acetyl-cysteine conjugates (SFN-NAC), which are excreted in the urine [22].…”
Section: Introductionmentioning
confidence: 99%